A Qualitative Study on Scopes and Gaps in Re-Branding Bangladesh Through Effective Communication - Tinny, Farhana Zamil; Dr. Bakare Akeem Soladoye (European Journal of Multidisciplinary Studies, 2019)
This study investigates the scopes and gaps that Bangladesh has in terms of re-branding her existing image throughout the world. Equally, the study also examines the consequences that Bangladesh is facing due to lack of effective communication. The topic has been chosen to find out all possible ways of correcting the existing negative image of Bangladesh around the world. To address the topic properly, the researchers have identified one general objective and five specific objectives. One of the objectives is to examine the importance of effective communication and how a well-planned effective communication can reduce existing gaps in re-branding Bangladesh. This research paper aims to find out that dedicated team, i.e. the opinion leaders of Bangladesh who can play a vital role in evoking the positive image in re-branding Bangladesh. This study also emphasizes on strengthening the scopes that can help the re-branding process more effectively. A qualitative research approach has been applied to conduct this research. The data has been collected through semi-structured in-depth interview and focus group discussions. While choosing the participants, the researchers used the purposive and the snow-ball methods to collect more verified data from the participants. Findings from the data analyzed show that Bangladesh lacks proper communication with both external and internal stakeholders. These gaps should be reduced in order to practice a proper and effective communication and to enhance a positive image of Bangladesh around the world.
Keywords: Bangladesh, effective communication, public relation, re-branding